Genocides and xenophobia in South Asia and beyond: a transdisciplinary perspective on known, lesser-known and unknown crime of crimes - Bhattacharyya, Rituparna (Routledge, 2023)
Understanding xenophobia and genocide / Rituparna Bhattacharyya -- Nationalisms on(the)line : new media and the fanning of fear and xenophobia / Aparajita De & Vivek Tripathi -- The alchemy of a sectarian riot : New Delhi, 2020 / Ajoy Ashirwad Mahaprashasta -- Genocide of Kashmiri Pandits / Kulbhushan Warikoo -- Narratives, violence and consent : the normalisation of state violence in Jammu & Kashmir / Devika Mittal -- Communal riot, pogrom, or genocide? Framing and naming the anti-Sikh violence of 1984 / Silvia Tieri -- Is Assam under the grip of a silent genocide? / Rituparna Bhattacharyya & Pranjit Sarma -- 'Recovering violent pasts' : revisiting moments of xenophobic violence and uprooting from partitioned North-east India / Binayak Dutta -- Genocide in Sylhet during the Liberation War of Bangladesh / Tulshi Kumar Das & Mohammad Jahirul Hoque -- Ethnic violence in Sri Lanka : politics of Sinhala-Tamil tensions / Roshni Kapur & Amit Ranjan -- Xenophobia in South Africa -- Can this morph into genocide? / Brij Maharaj & Steven Gordon -- 1994 Rwanda Holocaust : a critical analysis of xenophobia mutating to genocide against the Tutsis / Rituparna Bhattacharyya, Venkat Rao Pulla , Charles Kalinganire & Gaspard Rwanyiziri.